字典翻译 问答 小学 数学 【(根号A^2+A根号B)/(AB-B^2)-(A+根号AB+B)/(A根号A-B根号B)怎么化简?B^2=B²】
问题标题:
【(根号A^2+A根号B)/(AB-B^2)-(A+根号AB+B)/(A根号A-B根号B)怎么化简?B^2=B²】
问题描述:

(根号A^2+A根号B)/(AB-B^2)-(A+根号AB+B)/(A根号A-B根号B)怎么化简?

B^2=B²

霍明学回答:
  (根号A^2+A根号B)/(AB-B^2)-(A+根号AB+B)/(A根号A-B根号B)   =A(1+根号B)/(AB-B^2)-(A+根号AB+B)/[(根号A)^3-(根号B)^3]   =A(1+根号B)/(AB-B^2)-(A+根号AB+B)/[(根号A-根号B)(A+根号AB+B)]   =A(1+根号B)/(AB-B^2)-1/(根号A-根号B)   =A(1+根号B)/[B(A-B)]-(根号A+根号B)/(A-B)   =[A(1+根号B)-B(根号A+根号B)]/(A-B)   =(A-B根号B)/(A-B)
点击显示
数学推荐
热门数学推荐
  • 语文
  • 数学
  • 英语
  • 科学
  • 作文